THE STRATEGY OF RURAL TOURISM DEVELOPMENT (An Eco-economy and Eco-cultural Approach) - Amiluhur Soeroso; Y. Sri Susilo (Journal of Indonesian Economy and Business (JIEB), 2009)
The research is aimed to analyse the strategy of rural tourism development in Kepuharjo, a village in the foot plain of Merapi Volcano. The data were obtained from 140visitors doing activities surrounding Yogyakarta Special Province with structured questionnaire; the data was then analysed using conjoint analysis and analytic hierarchical process.The finding shows that the strategy of rural tourism development of Kepuharjo village is called “saga”. Within this strategy, its urgent aspect is keeping an evergreenenvironment, where the object has to be a conservatory value that almost disappears of environmental change. Besides, it must enrich the attractions, improve quality of amenities and get better of accessibilities. The implication of the finding, sustainable development of rural tourism of Kepuharjo Village, should use both an eco-economy way (designed to mesh with Earth's ecosystem instead of disrupting and destroying it) and an eco-culture work (to respects the traditional knowledge of existence and supports local materials and biodiversity) simultaneously.Keywords: strategy, rural tourism development, eco-economy, eco-culture.